SELF-NAMING PROFESSIONAL IN DANCE: QUESTIONS, PROBLEMS AND REPORTED (Fiep Bulletin - online, 2013)
This study aims to report cases of self-entitlement as professional dance teachers in the city of Rio de Janeiro, bureaucratic issues presented, and educational practices. How do the institutions that delegate actions teachers in dance activities not graduate teachers or experts in the field? And as the self titled work? We will analyze the reasons, difficulties and dangers of such action.
Keywords: Professional; Dance; self-Naming